An exploratory trial of intravenous immunoglobulin therapy for idiopathic pulmonary fibrosis: a preliminary multicenter report. (19th March 2015) - Enomoto, Noriyuki; Chida, Kingo; Suda, Takafumi; Kaida, Yusuke; Taniguchi, Masami; Azuma, Arata; Hayashi, Hiroki; Ogura, Takashi; Kitamura, Hideya; Yamaguchi, Ou; Ando, Masayuki; Sato, Atsuhiko; et al.
Abstract: Background and Aims: Idiopathic pulmonary fibrosis (IPF) is a fatal disorder without specific treatments. Although the efficacy of intravenous immunoglobulin (IVIG) therapy for autoimmune diseases has been reported, that for IPF remains unknown. This study aims to determine the efficacy and safety of IVIG for IPF. Methods: In an exploratory, multicenter, non‐randomized and prospective trial, patients with progressive IPF were enrolled. Patients were treated with IVIG for five consecutive days (5‐day IVIG) or once monthly for five consecutive months (5‐month IVIG). Changes in the vital capacity (VC), diffusion capacity of the lung for carbon monoxide (DLCO), 6‐min walk test (6MWT) and high‐resolution computed tomography (HRCT) findings were evaluated. Results: A total of 10 patients with IPF were treated with IVIG: 6 were in 5‐day IVIG and 4 were in 5‐month IVIG group. In 5‐day IVIG group, the treatment effects were temporal, and physiological and HRCT findings deteriorated in three of six patients. In 5‐month IVIG group, changes in %VC, %DLCO and walk distance in 6MWT at 6 months were −0.9 ± 5.3%, 6.9 ± 12.6% and 79 ± 58 m (mean ± standard deviation), respectively, and the treatment effects were long lasting. The change in VC 6 months after starting IVIG was smaller than that of 6–12 months after starting IVIG (after cessation of IVIG) (−0.02 ± 0.15 vs −0.33 ± 0.14 L, P  = 0.022). Ground glass opacities were diminished in two of four patients. Adverse events were mild and tolerable. Conclusion: This preliminary study shows that once‐monthly IVIG treatment may be effective and tolerable in patients with IPF.